Proceso de atención de enfermería en paciente de 65 años de edad con dengue - Bonilla Redroban, Mercy Paola (2021)
Dengue is a health problem with a growing proportion in the American continent, so it is important to understand primary care and management at other levels of care at the national level, to identify possible complications in each of them. The following case study is written in a 65-year-old patient with a history of hypothyroidism and chronic gastritis, who was admitted due to non-quantified pyrexia, asthenia, dynamic, arthralgia, myalgia, and nausea that evolved to vomiting on 5 occasions in the absence of mucus. , nor presence of hematic content, previously she received primary medical care by private means where they only alleviate symptoms and do not indicate diagnosis, after the aforementioned she goes to a type C health center for not obtaining clinical improvement of her symptoms and I monitor her for 2 hours continuous, vital signs were controlled and parenteral hydration and paracetamol 500 mg every 8 hours were induced, a venous sample was extracted in tubes for complete hematic biometry, in the obtained thrombocytopenia and leukopenia were evidenced, at the end of its surveillance the clinical picture does not improve, she is diagnosed with dengue and is referred to a level of greater complexity once in the area d e emergency, a new hematic biometry is performed, the diagnosis is confirmed and diclofenac and penicillin and azithromycin are administered orally, after which he received immediate hospitalization, with transfer to the internal medicine area 1, a urinalysis was performed and the results, ciprofloxacin 200 mg intravenously every 12 hours after the treatment, a new urinalysis was performed which gave normal results, it was decided to change the drug treatment to ceftriaxone 2 grams intravenously every 12 hours and a test was performed on the sixth day of hospitalization Serological for dengue, giving positive IgM results, the patient had blood tests every 72 hours. During her hospitalization, she would develop new signs and symptoms such as epigastralgia, eyelid edema, pruritus and dyspnea, the necks resolved adequately